2016
DOI: 10.15252/emmm.201505699
|View full text |Cite
|
Sign up to set email alerts
|

Red‐shifted channelrhodopsin stimulation restores light responses in blind mice, macaque retina, and human retina

Abstract: Targeting the photosensitive ion channel channelrhodopsin‐2 (ChR2) to the retinal circuitry downstream of photoreceptors holds promise in treating vision loss caused by retinal degeneration. However, the high intensity of blue light necessary to activate channelrhodopsin‐2 exceeds the safety threshold of retinal illumination because of its strong potential to induce photochemical damage. In contrast, the damage potential of red‐shifted light is vastly lower than that of blue light. Here, we show that a red‐shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
190
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(194 citation statements)
references
References 51 publications
2
190
1
1
Order By: Relevance
“…In these experiments transduction was wide-spread and similar for all capsid variants contrasting previous studies that reported successful transduction of human explants only in the parafoveal region and along blood vessels (Sengupta et al, 2016). In line with the fact that the morphology of the eyes of mouse and human differ, the overall cell transduction pattern differed, with marked expression in the photoreceptor cells of human explants.…”
Section: Discussioncontrasting
confidence: 80%
“…In these experiments transduction was wide-spread and similar for all capsid variants contrasting previous studies that reported successful transduction of human explants only in the parafoveal region and along blood vessels (Sengupta et al, 2016). In line with the fact that the morphology of the eyes of mouse and human differ, the overall cell transduction pattern differed, with marked expression in the photoreceptor cells of human explants.…”
Section: Discussioncontrasting
confidence: 80%
“…About 50% of the hCAR + cells were found to express detectable levels of Jaws-GFP in this foveola. The other half of the retina was conserved as explants (34) for characterization of optogenetic light responses arising from the hyperpolarizing pump Jaws ( Figure 5, F-K). Electrophysiological recordings were performed on transduced cones expressing Jaws and in control cones without Jaws expression (Figure 5, F and G).…”
Section: Resultsmentioning
confidence: 99%
“…We previously validated the L-AP4 blockade of all ON responses in wild-type retinas in both mouse, macaque, and human retinas. 11,15 At the single-cell level, cell-attached recordings revealed ON light responses under 1.46 10 16 photons/cm 2 /s at 470 nm in RGCs from the AAV2-SNCG-CatCh-GFP retina and in the retinas from NHP2 infected with AAV2-SNCG-CatCh without GFP, which were recorded without assistance by fluorescent labeling ( Figure 4B, left and center/ top right). In all patched cells under whole-cell configuration, we observed typical channelrhodopsin-evoked photocurrents consisting of a fast transient current followed by a steady-state current at a holding potential of À60 mV ( Figure 4B, bottom right).…”
Section: Electrophysiological Recordings Reveal Catch-driven Responsementioning
confidence: 99%
“…Retinas were isolated upon arrival, and the perifoveal area was cut into square-shaped pieces (approximately 4-5 mm) and cultured in Neurobasal medium complemented with B27 serum-free supplement (Life Technologies) on Transwell permeable culture support (Corning) as previously described. 15 Primate retinal explants were left to rest in an incubator 1-2 days prior to MEA recordings. Isolated retinas were placed on a cellulose membrane and gently pressed against an MEA (MEA256 100/30 iR-ITO; Multichannel Systems), with the RGCs facing the electrodes.…”
Section: Mea Recordings Of Isolated Retinasmentioning
confidence: 99%
See 1 more Smart Citation